Emerging membrane technology for sustainable water treatment - Hankins, Nicholas P.; Singh, Rajindar 1947- (Elsevier, 2016)
Emerging Membrane Technology for Sustainable Water Treatment provides the latest information on the impending crisis posed by water stress and poor sanitation, a timely issue that is one of the greatest human challenges of the 21st century. The book also discusses the use of membrane technology, a serious contender that can be used to confront the crisis on a global scale, along with its specific uses as a solution to this escalating problem.--Provided by publisher.